ChemInform Abstract: Hydrothermal Synthesis and Structural Characterization of an Organic‐Inorganic Hybrid Sandwich‐Type Tungstoantimonate [Cu(en)2(H2O)]4 [Cu(en)2(H2O)2] [Cu2Na4 (α‐SbW9O33)2]·6H2O. Issue 8 (25th February 2014) - Liu, Yingjie; Cao, Jing; Wang, Yujie; Li, Yanzhou; Zhao, Junwei; Chen, Lijuan; Ma, Pengtao; Niu, Jingyang
Abstract The title compound is synthesized by hydrothermal reaction of Sb2O3, Na2WO4, CuCl2, and en (autoclave, 160 °C, 6 d; 30% yield based on Sb2O3).